FINANCIAL RATIO ANALYSIS OF PT BARRAMULTI SUKSESSARANA TBK - Isbachatul Mubarokah; Nosilia Fristanti (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to evaluate the financial performance of PT Baramulti Sukses Sarana (BSSR) using a quantitative descriptive approach based on the company’s financial statements for the 2019–2024 period. Methods: The research analyzes financial trends over time through horizontal analysis and examines key financial ratios, including liquidity, solvency, activity, and profitability. Secondary data were obtained from the official website of the Indonesia Stock Exchange, while additional information was collected from the company’s published annual financial reports. Results: The findings show that BSSR maintains a strong liquidity position, as indicated by a consistently high current ratio throughout the period of observation. Solvency analysis through the debt-to-equity ratio demonstrates that the company is managing its capital structure in a stable and sustainable manner. Activity ratios, such as fixed asset turnover and total asset turnover, indicate efficient utilization of assets in generating revenue. Profitability ratios, including net profit margin and return on assets, reflect the company’s ability to generate favorable financial returns despite fluctuations in coal market conditions. Overall, the study concludes that BSSR exhibits sound financial performance, supported by effective asset management, balanced leverage, and consistent profitability. The results highlight the importance of maintaining liquidity strength and operational efficiency to ensure long-term financial stability and competitiveness in the mining sector. Keywords: Activity; Financial Ratios, Liquidity; Profitability; Solvency;